1995
DOI: 10.1111/j.1532-5415.1995.tb07005.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density, Vitamin D Nutrition, and Parathyroid Hormone Levels in Women with Dementia

Abstract: We conclude that there were no significant differences in the bone density of community-dwelling women with mild dementia compared with normals. However, there were significant differences in parathyroid hormone and vitamin D levels between the two groups, suggesting that there is a high prevalence of subclinical hypovitaminosis D in demented women in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 20 publications
3
61
1
Order By: Relevance
“…There is a higher prevalence of falls and fractures in patients with Alzheimer's Disease (Buchner and Larson 1987) and community studies have shown that residents with Alzheimer's Disease and dementia had lower serum concentrations of 25(OH)D (Kipen, Helme et al 1995;Sato, Asoh et al 1998). While the temporal association of these findings remains unclear, in a study in patients with Alzheimer 's disease, 25(OH)D concentrations were significantly elevated after year-round sun exposure.…”
Section: Vitamin D and Alzheimer's Diseasementioning
confidence: 97%
“…There is a higher prevalence of falls and fractures in patients with Alzheimer's Disease (Buchner and Larson 1987) and community studies have shown that residents with Alzheimer's Disease and dementia had lower serum concentrations of 25(OH)D (Kipen, Helme et al 1995;Sato, Asoh et al 1998). While the temporal association of these findings remains unclear, in a study in patients with Alzheimer 's disease, 25(OH)D concentrations were significantly elevated after year-round sun exposure.…”
Section: Vitamin D and Alzheimer's Diseasementioning
confidence: 97%
“…Among 20 women with mild dementia, 25-hydroxyvitamin D was significantly lower compared with 40 age-matched cognitively normal female controls [13]. A decrease of 25-hydroxyvitamin D was observed in a Japanese study of 58 patients with severe and 42 patients with mild Alzheimer's disease in comparison with 100 age-matched community dwelling controls [14].…”
Section: Small-scale Case-control and Cohort Studiesmentioning
confidence: 99%
“…Clinical data show a linkage between low levels of 1,25-(OH) 2 D 3 and cognitive deterioration (Katzman et al, 1983;Morris, 1993), particularly in Alzheimer's disease patients (Kipen et al, 1995;Sato et al, 1998). Vitamin D deficiency is associated with low mood and worse cognitive performance in the elderly (Wilkins et al, 2006).…”
Section: Introductionmentioning
confidence: 96%